Germination response of grasspea (Lathyrus Sativus L/) and arugula (Eruca Sativa L.) to osmotic and salinity stresses - Fallahi , Hamid-Reza; Fadaeian , Golsoom; Gholami , Marziyeh; Daneshkhah , Omolbanin; Hosseini , Fatemeh Sadat; Aghhavani-Shajari, Mahsa; Samadzadeh , Alireza (Plant Breeding and Seed Science, 2015)
The use of genetic potential of forgotten plants such as grasspea and arugula is an appropriate strategy for increasing of plants tolerance to environmental stresses. Therefore, in this laboratory study the effects of different levels of osmotic (0, -2, -4, -6, -8, -10, -12 and -14 bar caused by PEG) and salinity (0, 50, 100, 150, 200, 250, 300 and 350 mmol induced by NaCl) stresses were evaluated on germination indices of grasspea and arugula in four separate experiments. Arugula showed a suitable tolerance to osmotic stress, so that its germination percentage and rate at treatment of -10 bar were similar to control. Arugula had 79% germination at osmotic level of -14 bar, but its germination rate at this level was 60% lower than control. In addition, its radicle length until -8 bar and radicle dry weight up to -14 bar were higher than control treatment. However, all levels of salinity stress particularly treatments of more than 100-150 mmol decreased the germination indices of arugula. Germination percentage of arugula in 150 and 200 mmol treatments was 22 and 56% lower than control treatment, respectively. Grasspea had partially suitable tolerance to osmotic stress until -6 bar, but then intensified the reducing trends of its germination indices and finally reached to zero at -14 bar treatment. Moreover, salinity stress especially treatments of higher than 100 mmol decreased all germination indices of grasspea. Overall, arugula was a more tolerant plant especially to osmotic stress; therefore this forgotten plant can be used in agronomic and breeding programs in areas affected by drought stress